2016
DOI: 10.1016/j.jngse.2016.09.068
|View full text |Cite
|
Sign up to set email alerts
|

Applications of nano-indentation methods to estimate nanoscale mechanical properties of shale reservoir rocks

Abstract: In order to study the mechanical properties of shale samples from Bakken Formation, nanoindentation method, an imaging technique borrowed from other engineering disciplines, was used. Different types of nanoindentation curves were analyzed and the applicability of the nanoindentation theories to study mechanical properties of shale samples at nanoscale was demonstrated. Elastic modulus and Hardness of different samples were calculated, compared and related to their mineral compositions and microstructures whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(53 citation statements)
references
References 30 publications
3
45
0
Order By: Relevance
“…The preparation of samples was mainly based on available protocols (ISO14577,2015) and the work of Liu et al [50,51], but we made some improvements in the polishing process to ensure the smoothness of surface. Three samples (shown in Figure 2) were broken into small pieces to make the testing surfaces parallel to the bedding plane.…”
Section: Methodsmentioning
confidence: 99%
“…The preparation of samples was mainly based on available protocols (ISO14577,2015) and the work of Liu et al [50,51], but we made some improvements in the polishing process to ensure the smoothness of surface. Three samples (shown in Figure 2) were broken into small pieces to make the testing surfaces parallel to the bedding plane.…”
Section: Methodsmentioning
confidence: 99%
“…During the drilling process, the drill bit may pass through greatly varying geologies, which may be reflected in their different properties. Even within a single rock type, the properties can vary markedly, as shown by various workers who used techniques such as nanoindentation and atomic force microscopy (AFM) to map the variation in properties of a wide range of rocks [27][28][29][30][31][32][33][34][35][36][37][38][39]. In granite, which is often used in laboratory-based trials of PDC cutters (see below), Heinrichs et al [35] showed wide variations in hardness of the three major constituents: quartz (H = 13 ± 1.0 GPa), feldspar (H = 10 ± 1.0 GPa), and biotite (H = 3.4 ± 1.3 GPa).…”
Section: Geology Of Hydrocarbon Reservoirsmentioning
confidence: 99%
“…Measurements made by nanoindentation showed widely varying mechanical behavior, ranging from hard quartz inclusions to softer clay constituents. Liu et al [32] performed nanoindentation on shale samples taken from the Bakken Formation, North Dakota, an area of considerable interest for hydrocarbon exploration via hydraulic fracturing. The rocks examined were found to consist principally of quartz and clay minerals (mainly illite).…”
Section: Geology Of Hydrocarbon Reservoirsmentioning
confidence: 99%
“…The scaling relationships of reduced modulus, hardness and energy were evaluated by experimental verification and theoretical analysis. By analyzing the change of indentation fracture work, Liu et al investigated the relationship between fracture energy and fracture toughness [15]. The relationships of total energy, fracture energy and irreversible energy were further discussed, and the solution of fracture toughness was optimized.…”
Section: Introductionmentioning
confidence: 99%